Private Sponsorship of Rural Development Broadcasts on Radio in Southwest Nigeria - I O Badiru; A E Adekoya (Journal of Agricultural Extension, 2014)
The study explored the private sponsorship prospects of rural development broadcasts (RDBs) on radio in Southwest Nigeria. Forty private sponsors of programmes were randomly selected for the study. Questionnaire was used to collect data on private sponsorship status of RDBs, reasons for broadcasts’ sponsorship, factors hindering RDBs sponsorship and willingness to sponsor RDBs. Frequency counts and binomial logit were used to analyse the resulting data. There was a low sponsorship status (26.7%) of RDBs among the sponsors. Inadequate knowledge of benefits derivable from sponsorship of RDBs (30%) hindered sponsorship of RDBs while increased sensitisation on these benefits (40%) would enhance their sponsorship status. Increased brand awareness was the most important reason (46.7%) that propelled sponsors to support broadcasts. Most sponsors (66.7%) would be willing to support RDBs on radio. Sponsors’ characteristics were not significantly related to their willingness to sponsor RDBs. Stakeholders in rural development broadcasting should therefore step up their sensitisation campaigns among prospective sponsors to intimate them of the listenership strength of RDBs in the area in order to improve the sponsorship situation.